Hubungan antara Gaya Kepemimpinan Partisipatif Vroom-Yetton dan Motivasi Belajar Siswa di Lembaga Pendidikan Indonesia - Faujiah, Hikmatul; Gunawan, Agus; Syarifudin, Encep (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This literature review research aims to explore the relationship between the Vroom-Yetton participatory leadership style and students' motivation to learn at school. The method used is an analysis of empirical studies and the latest literature relevant to the research topic. The results showed that the Vroom-Yetton participatory leadership style had a positive impact on students' learning motivation at school. This leadership style involves active participation of students in making decisions related to learning programs and the learning environment. Students are given the opportunity to express their opinions, provide feedback, and make decisions together with educational leaders and teachers. This study shows that students who are involved in decision-making and are given an active role in learning feel more valued and have a sense of ownership of their learning. This can increase students' learning motivation and help them to achieve their academic goals. In addition, the Vroom-Yetton participatory leadership style also allows teachers to obtain better feedback from students regarding their learning experiences. Teachers can use this feedback to modify the learning program and learning environment according to the needs of students, thereby increasing their motivation to learn. In conclusion, this study shows that the Vroom-Yetton participatory leadership style can have a positive impact on students' motivation to learn at school. Therefore, educational leaders should consider implementing the Vroom-Yetton participatory leadership style in learning environments to increase students' motivation to learn and the overall quality of education. Further studies can be conducted to explore more deeply the impact of the Vroom-Yetton participatory leadership style on student motivation in different educational environment.